2018
DOI: 10.1115/1.4038854
|View full text |Cite
|
Sign up to set email alerts
|

Dropwise Condensation on Superhydrophobic Microporous Wick Structures

Abstract: Previous research in dropwise condensation (DWC) on rough microtextured superhydrophobic surfaces has demonstrated evidence of high heat transfer enhancement compared to smooth hydrophobic surfaces. In this study, we experimentally investigate the use of microporous sintered copper powder on copper substrates coated with a thiol-based self-assembled monolayer to attain enhanced DWC for steam in a custom condensation chamber. Although microtextured superhydrophobic surfaces have shown advantageous droplet growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The results of the existing simulations (Rose, 2002) and experiments (Alwazzan et al, 2017, Hoenig, and Bonner, 2018, O'Neill, and Westwater, 1984 are also shown in Fig. 6, with good agreement with the predictions of this study.…”
Section: Size-effect Regime Diagramsupporting
confidence: 85%
“…The results of the existing simulations (Rose, 2002) and experiments (Alwazzan et al, 2017, Hoenig, and Bonner, 2018, O'Neill, and Westwater, 1984 are also shown in Fig. 6, with good agreement with the predictions of this study.…”
Section: Size-effect Regime Diagramsupporting
confidence: 85%
“…Further observations show that the departing droplet size appears to be the primary variable governing heat transfer, in addition to secondary explanations, such as the droplet growth mode, conduction resistance, and filmwise modes of condensation underneath the powder structures. These findings are in reference to [28], which the subsequent departing droplet size observations are exclusively based on. In this complementary study by Hoenig et al, the maximum departing droplet sizes were measured for several departing droplets located near the top of all of the condensation surfaces.…”
Section: Departing Droplet Sizementioning
confidence: 76%
“…It was found that heat transfer coefficient greatly depends on microporous powder diameter. As the diameter decreases, htc increases; for a 4-µm diameter, 23% htc increment was reported as compared to bare surface [168]. However, the improvement is low as compared to other coating techniques.…”
Section: Porous Coatingsmentioning
confidence: 92%
“…The disadvantage of SLIPS are their durability; after a certain time, liquid infusion diminishes, and due to condensate pinning, htc decreases [166]. Attempts have been made to develop microporous surfaces along with SAMs [167,168]. It was found that heat transfer coefficient greatly depends on microporous powder diameter.…”
Section: Porous Coatingsmentioning
confidence: 99%